The Urgency Of Islamic Religious Education In The Formation Of Children's Character and Karimah In The Family Environment - Ahmad Nilnal Munachifdlil Ula; Muhammad Shihabbuddin (IJGIE (International Journal of Graduate of Islamic Education), 2024)
The aim The aim of writing this article is to 1) find out how Islamic religious education in the family can be introduced, 2) instill Islamic religious education in the family environment, 3) form good morals in the family environment through Islamic religious education. Type of research used in the articleis a type of library research, while the research method is analytical descriptive. Data was obtained through journals, books, theses and others. The results of the discussion show thatThere are three types of Islamic religious education within the family environment, namely: faith education, worship education and akhlakul karimah education. Instilling Islam in the family environment can be done through several strategies, including: cooperation, performance or practice, example, commands and prohibitions, rewards and punishments. Education religion Islam in the family environment has urgency in the formation of children's morals because the family is the smallest institution in the socialization of Islamic religious values. It is also the first place where children learn about religion and its teachings. Through education...This in children in the family environment will shape the child's morals so that they become human beings, namely human beings who relate good to Allah (hablumminallah) and humans who have good relationships with, man.and nature (hablumminannas wal alam).